2016
DOI: 10.1038/ncomms12217
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic stratification in electroactive biofilms of Geobacter sulfurreducens mediated by pilus nanowires

Abstract: Electricity generation by Geobacter sulfurreducens biofilms grown on electrodes involves matrix-associated electron carriers, such as c-type cytochromes. Yet, the contribution of the biofilm's conductive pili remains uncertain, largely because pili-defective mutants also have cytochrome defects. Here we report that a pili-deficient mutant carrying an inactivating mutation in the pilus assembly motor PilB has no measurable defects in cytochrome expression, yet forms anode biofilms with reduced electroactivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
179
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(194 citation statements)
references
References 60 publications
11
179
4
Order By: Relevance
“…NuoL, for which metagenomic rank changed most at the M4 anode compared to M1A, is responsible for the reverse electron transfer and H + /estoichiometry (Steimle et al, 2011), which may be important for balancing electron flow between NAD+ and ferredoxin pools. PilB is an ATPase required for polymerization of conductive e-pili (McCallum et al, 2017), and pilB mutants are reported to generate lower current and form thinner biofilms (Steidl et al, 2016). Additionally, it was observed by Ishii et al (2018) that pilA expression increased at lower surface potential.…”
Section: Presence Of Geobacter Spp At Cathodesmentioning
confidence: 99%
“…NuoL, for which metagenomic rank changed most at the M4 anode compared to M1A, is responsible for the reverse electron transfer and H + /estoichiometry (Steimle et al, 2011), which may be important for balancing electron flow between NAD+ and ferredoxin pools. PilB is an ATPase required for polymerization of conductive e-pili (McCallum et al, 2017), and pilB mutants are reported to generate lower current and form thinner biofilms (Steidl et al, 2016). Additionally, it was observed by Ishii et al (2018) that pilA expression increased at lower surface potential.…”
Section: Presence Of Geobacter Spp At Cathodesmentioning
confidence: 99%
“…Transmembrane electron flow across the envelope relies on cyt clusters such as OmaB-OmcB, OmaC-OmcC, extA-extC/D, and extG-extF, each of which is integrated with a porin for protein localization (Otero, Chan, & Bond, 2018;Shi et al, 2016). For long range electron transfer in the exterior space of cells, redox proteins including OmcE, OmcS, and OmcZ and conductive pili are involved as electron relay and/or terminal reductases (Steidl, Lampa-Pastirk, & Reguera, 2016;Vargas et al, 2013). Besides, other redox proteins may be used when these proteins are absent in mutants (Aklujkar et al, 2013;Mehta, Childers, Glaven, Lovley, & Mester, 2006;Otero et al, 2018).…”
mentioning
confidence: 99%
“…The Nernst-Monod equationa ssumes Ohm's law for EET. [8,65] In contrast, recent publications reported that the conductivity of Geobacter sulfurreducens biofilms increased with increasing temperature and water content, [60,61] supporting redox conduction among extracellularc ofactors (e.g.,c ytochromes) for EET. EET conduction mechanismsa re still on debate between metallic-like and redox conduction for the Geobacter sulfurreducens biofilm anode.…”
Section: Extracellular Electron-transfer Kineticsmentioning
confidence: 91%
“…This metal-like conduction attributed from p-p stacking of aromatic amino acids in Geobacter's pili or nanowire. [8,65] In contrast, recent publications reported that the conductivity of Geobacter sulfurreducens biofilms increased with increasing temperature and water content, [60,61] supporting redox conduction among extracellularc ofactors (e.g.,c ytochromes) for EET. It seems that Geobacter sulfurreducens biofilms would have multiple conduction mechanisms for EET to electrodes, which implies that EET conduction mechanismsw ould be more complicated in Geobacter-enriched mixed cultureb iofilms.…”
Section: Extracellular Electron-transfer Kineticsmentioning
confidence: 91%